2009
DOI: 10.1002/lt.21857
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic variceal ligation for primary prophylaxis of esophageal variceal hemorrhage in pre-liver transplant patients

Abstract: Endoscopic variceal ligation (EVL) is widely used to prevent esophageal variceal bleeding in patients with advanced cirrhosis. However, the safety and efficacy of EVL in this setting have not been clearly established. This study included 300 adult patients with cirrhosis on our liver transplant waitlist who underwent upper gastrointestinal endoscopy. Esophageal varices deemed to be at high risk of bleeding were banded until eradication or transplantation. A retrospective review of patient notes and endoscopy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…There were no statistically significant differences between group I and group II regarding all sonographic data e.g. liver size, portal vein diameter, presence and amount of ascites and spleen size as shown in table (3). Table ( 4) shows that, there are no statistically significant baseline differences between cases and controls regarding laboratory parameters including (hemoglobin concentration, total leukocytic count, platelet count, albumin level, total and direct bilirubin levels), ALT, AST, PT, INR, and serum creatinine level.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…There were no statistically significant differences between group I and group II regarding all sonographic data e.g. liver size, portal vein diameter, presence and amount of ascites and spleen size as shown in table (3). Table ( 4) shows that, there are no statistically significant baseline differences between cases and controls regarding laboratory parameters including (hemoglobin concentration, total leukocytic count, platelet count, albumin level, total and direct bilirubin levels), ALT, AST, PT, INR, and serum creatinine level.…”
Section: Resultsmentioning
confidence: 81%
“…Although 50% of all esophageal variceal bleeding episodes stop spontaneously, the rebleeding rate is high with about 50% of patients experiencing a second episode, usually within 2 weeks from the first episode. A second episode of bleeding puts the patient at a high mortality risk and is thus the reason for starting therapy as soon as possible [3]. Endoscopic sclerortherapy should be performed early after hospital admission, assuring that the patient is resuscitated and hemodynamically stable [4].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Endoscopic variceal band ligation (EVL) is associated with band-induced ulceration bleeding in 1.2 to 7.3% of patients. 31,32 Lim et al reported the lowest rate of bleeding of 1.2% (3/258) from retrospective chart review of patients undergoing EVL for primary prophylaxis in patients awaiting liver transplantation (LT). 32 A prospective study of unselected patients (primary and secondary prophylaxis with varying disease severity) reported a higher incidence of bleeding of 7.3% (11/150) post EVL.…”
Section: Procedural Bleedingmentioning
confidence: 99%
“…31,32 Lim et al reported the lowest rate of bleeding of 1.2% (3/258) from retrospective chart review of patients undergoing EVL for primary prophylaxis in patients awaiting liver transplantation (LT). 32 A prospective study of unselected patients (primary and secondary prophylaxis with varying disease severity) reported a higher incidence of bleeding of 7.3% (11/150) post EVL. 31 They noted a higher incidence with increased disease severity (17% in CPC C vs. 4…”
Section: Procedural Bleedingmentioning
confidence: 99%
“…Small blood vessels exude from red spots that are pinhead-sized. Fluid buildup in the legs and feet (edema) and in the abdomen (ascites), itching, occasionally reddish and blotchy palms, a condition known as palmar erythema are some of the symptoms that start to develop as cirrhosis progresses to the decompensated stage., swelling of breasts or shrinkage of the testicles may occur in men, as well as easy bruising and excessive bleeding (Lim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%